2019
DOI: 10.1016/j.jeurceramsoc.2019.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Material removal mode and friction behaviour of RB-SiC ceramics during scratching at elevated temperatures

Abstract: Thermal-assistant is considered potentially as an effective approach to improve machinability of hard and brittle materials. Understanding the material removal and friction behaviour influenced by the purposely introduced heat is crucial to obtain high quality machined surface. This paper aims to reveal material removal and friction behaviours of RB-SiC ceramics scratched by a Vickers indenter at elevated temperatures. Material removal mode, scratching hardness, critical depth of ductile-brittle transition, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Additionally, a pristine RB-SiC sample was polished with a diamond slurry having a particle size of 0.25 μm until a surface finish of 20 nm (Sa) was obtained, which was used to determine the subsurface damage in the EDDG process through comparison. In a previous study [24], X-ray diffraction analysis revealed that an RB-SiC sample primarily consisted of 6H-SiC phases. The main properties of the RB-SiC supplied by Goodfellow Cambridge Ltd. are listed in Table 1.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, a pristine RB-SiC sample was polished with a diamond slurry having a particle size of 0.25 μm until a surface finish of 20 nm (Sa) was obtained, which was used to determine the subsurface damage in the EDDG process through comparison. In a previous study [24], X-ray diffraction analysis revealed that an RB-SiC sample primarily consisted of 6H-SiC phases. The main properties of the RB-SiC supplied by Goodfellow Cambridge Ltd. are listed in Table 1.…”
Section: Methodsmentioning
confidence: 85%
“…The discharge energy transferred to the workpiece changes the material properties of RB-SiC in the grinding zone, affecting the critical depth hc. In a previous study [24],…”
Section: Surface and Subsurface Damage Induced By The Interactionsmentioning
confidence: 88%
“…In general, the friction force between indenter and groove surface is equal to the sum of the adhesion force and the ploughing force in the nanoscratching test [40,41], namely…”
Section: Theoretical Cof Model For Edge-forward and Face-forward Nanomentioning
confidence: 99%
“…In the previous work [21,25], depth of cut. The ductile material removal mode can be obtained as the actual depth of cut is less than the critical depth of cut given by [26]:…”
Section: Machined Surface Integritymentioning
confidence: 99%
“…However, Eq. (1) has been modified by considering the variation of mechanical property at elevated temperatures in the previous work [25], which is given by:…”
Section: Machined Surface Morphologymentioning
confidence: 99%